NEW GOUT CLASSIFICATION CRITERIA (ACR/EULAR 2015) - N. T. Vatutin; G. S. Smyrnova; M. A. El-Khatib (Архивъ внутренней медицины)
Gout new diagnostic criteria are reflected in the presented translation of new international guidelines (ACR/EULAR 2015).